2015
DOI: 10.5194/angeo-33-117-2015
|View full text |Cite
|
Sign up to set email alerts
|

Pc2-3 geomagnetic pulsations on the ground, in the ionosphere, and in the magnetosphere: MM100, CHAMP, and THEMIS observations

Abstract: Abstract. We analyze Pc2-3 pulsations recorded by the CHAMP (CHAllenging Minisatellite Payload) satellite in the F layer of the Earth's ionosphere, on the ground, and in the magnetosphere during quiet geomagnetic conditions. The spectra of Pc2-3 pulsations recorded in the F layer are enriched with frequencies above 50 mHz in comparison to the ground Pc2-3 spectra. These frequencies are higher than the fundamental harmonics of the field line resonances in the magnetosphere. High quality signals with dominant fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Processes in the geomagnetic tail, which may be related to any pre-substorm signatures, are reflected mostly in broadband, high-latitude, long-period ULF fluctuations. Such "geomagnetic noise" requires a quantitative analysis technique, such as that developed by Yagova et al (2010Yagova et al ( , 2015. Yagova et al (2010) found that the spectral content of high-latitude geomagnetic pulsations in the 1-5 mHz (Pc5/Pi3) frequency range is characterized by regular diurnal variation and irregular day-to-day variation.…”
Section: Reported a Uniquementioning
confidence: 99%
See 1 more Smart Citation
“…Processes in the geomagnetic tail, which may be related to any pre-substorm signatures, are reflected mostly in broadband, high-latitude, long-period ULF fluctuations. Such "geomagnetic noise" requires a quantitative analysis technique, such as that developed by Yagova et al (2010Yagova et al ( , 2015. Yagova et al (2010) found that the spectral content of high-latitude geomagnetic pulsations in the 1-5 mHz (Pc5/Pi3) frequency range is characterized by regular diurnal variation and irregular day-to-day variation.…”
Section: Reported a Uniquementioning
confidence: 99%
“…PSDs, and the magnetic-auroral cross spectra (in both square coherence and phase difference) are calculated for the two horizontal components of the magnetic field and the 557.7 nm MSP channel. In addition to the cross-spectral analysis, a quantitative description of broad-band pulsations is carried out using the methods described in Yagova et al (2010Yagova et al ( , 2015 and the reader is directed to those papers for a more detailed description. Briefly, the technique is based upon an expansion into Legendre polynomials of a log-log spectrum with the resulting coefficients providing a quantitative description of ULF wave activity.…”
Section: Data Processingmentioning
confidence: 99%
“…Moreover, Yagova et al (2015) observed ground-toionosphere ULF wave amplitude ratios between MM100 ground magnetometer network stations and the CHAMP satellite, corresponding to a Doppler shift f = 6.4 mHz (i.e. within a few percent of the apparent frequency of the Pc2-3 pulsations recorded by a low-orbiting spacecraft).…”
Section: Discussionmentioning
confidence: 93%
“…In another study Balasis et al (2012) showed that the simultaneous activation of pulsations in the Pc3 and Pc5 frequency ranges in the magnetosphere is possible. If the amplitudes of Pc3 waves in the F layer are within several tenths of a nanotesla and their wavelengths k ≥ 10 −2 km −1 , only Pc3 waves would be recorded by an ionospheric satellite due to its high speed, and only Pc5 waves would be seen on the ground surface because of the effective ionospheric attenuation of Pc3 activity (Yagova et al, 2015). This means that synchronous recording of ground Pc5 pulsations and ionospheric Pc3 waves does not necessarily indicate that the ionospheric signal is a Doppler-shifted Pc4-5.…”
Section: Discussionmentioning
confidence: 99%
“…A number of magnetic and electric field missions flying in a low-Earth orbit (LEO), like CHAMP, Ørsted, SAC-C, or ST5, have enabled us to study in situ the occurrence of ULF waves in the topside ionosphere. In particular, ULF wave monitoring from LEO satellites has been most prominently reported in the Pc3 frequency range (f 20-100 MHz) (e.g., Jadhav et al, 2001;Vellante et al, 2004;Heilig et al, 2007Heilig et al, , 2013Ndiitwani and Sutcliffe, 2009;Le et al, 2011;Balasis et al, 2012Balasis et al, , 2015aChi and Le, 2015;Yagova et al, 2015), while for Pc1 waves (e.g., Engebretson et al, 2008;Park et al, 2013a) and Pi2 waves (f 2-25 MHz) (e.g., Sutcliffe and Lühr, 2003) there have been fewer studies.…”
Section: Introductionmentioning
confidence: 99%